The factors influencing job satisfaction of other ranks personnel in Royal Malaysian Navy - Shamsul Amery, Zainuddin (2017)
Job satisfaction is an important factor and should be a priority for other ranks personnel of Royal Malaysian Navy (RMN). However, job satisfaction is one aspect that is very relative and subjective to every employee. Thus, these feelings arise when someone wants to do the job and it varies between employees. The main objective of this study is to examine factors that influence job satisfaction of the other ranks personnel in the Royal Malaysian Navy (RMN). Generally, the study will focus to determine whether nature of the job, work environment, compensation, career advancement and supervision influencing to the job satisfaction. 438 respondents involved in this study from four major bases of Royal Malaysian Navy (RMN). The result of study showed nature of the job, work environment, compensation, career advancement and supervision have a significant influence to job satisfaction among the other ranks in the RMN (r = 0.751, r2 = 0.564, p = 0.000). This result indicates that 56.4% of job satisfaction of the other ranks personnel in Royal Malaysian Navy (RMN) is influenced by independent variables. This study plays a vital role in influence the organization and policy makers to think over the employee job satisfaction. The findings of this research are valuable, which can be useful in order to improve employee job satisfaction. Therefore, the Royal Malaysian Navy (RMN) organization should consider the nature of job, working condition, compensation, career advancement and supervision as the factors that will influence job satisfaction among their other ranks personnel.